2017
DOI: 10.24920/j1001-9294.2017.046
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Application of WCX Magnetic Bead-Based Matrix-Assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry in Analyzing the Urine of Renal Clear Cell Carcinoma

Abstract: Objective To evaluate the application of weak cation exchange (WCX) magnetic bead-based MatrixAssisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) in detecting differentially expressed proteins in the urine of renal clear cell carcinoma (RCCC) and its value in the early diagnosis of RCCC.Methods Eleven newly diagnosed patients (10 males and 1 female, aged 46-78, mean 63 years) of renal clear cell carcinoma by biopsy and 10 healthy volunteers (all males, aged 25-32, mean 29.7 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…For the first time, regarding this specific subtype of cancer, a non-invasive procedure was used to identify urinary biomarkers. On the other hand, Dong et al [17] used bead-based MALDI-TOF MS to discover 160 potential protein biomarkers in urines from 10 HCs and 11 newly diagnosed patients with renal clear cell carcinoma. Similarly, Wang et al [18] identified 76 different urinary polypeptides, using MALDI-TOF MS to establish the peptide expression biosignatures of 34 patients with lung adenocarcinoma and 36 HCs to serve as potential biomarkers to non-invasively detect lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, regarding this specific subtype of cancer, a non-invasive procedure was used to identify urinary biomarkers. On the other hand, Dong et al [17] used bead-based MALDI-TOF MS to discover 160 potential protein biomarkers in urines from 10 HCs and 11 newly diagnosed patients with renal clear cell carcinoma. Similarly, Wang et al [18] identified 76 different urinary polypeptides, using MALDI-TOF MS to establish the peptide expression biosignatures of 34 patients with lung adenocarcinoma and 36 HCs to serve as potential biomarkers to non-invasively detect lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical symptoms of RCCC are not specific and are often ignored or misdiagnosed [ 5 ]. Therefore, it is significant to find biomarkers that can accurately predict the prognosis of RCCC patients [ 6 ]. Recently, with the continuous development of genomics and bioinformatics technologies, many studies have shown that prognostic biomarkers can provide clinicians with the basis for prognosis evaluation, thereby guiding patient treatment options and prognosis management [ [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%